A drug screen with approved compounds identifies amlexanox as a novel Wnt/β‐catenin activator inducing lung epithelial organoid formation. (31st July 2021) - Costa, Rita; Wagner, Darcy E.; Doryab, Ali; De Santis, Martina M.; Schorpp, Kenji; Rothenaigner, Ina; Lehmann, Mareike; Baarsma, Hoeke A.; Liu, Xueping; Schmid, Otmar; Campillos, Monica; Yildirim, Ali Önder; et al.
Abstract : Background and Purpose: Emphysema is an incurable disease characterized by loss of lung tissue leading to impaired gas exchange. Wnt/β‐catenin signalling is reduced in emphysema, and exogenous activation of the pathway in experimental models in vivo and in human ex vivo lung tissue improves lung function and structure. We sought to identify a pharmaceutical able to activate Wnt/β‐catenin signalling and assess its potential to activate lung epithelial cells and repair. Experimental Approach: We screened 1216 human‐approved compounds for Wnt/β‐catenin signalling activation using luciferase reporter cells and selected candidates based on their computationally predicted protein targets. We further performed confirmatory luciferase reporter and metabolic activity assays. Finally, we studied the regenerative potential in murine adult epithelial cell‐derived lung organoids and in vivo using a murine elastase‐induced emphysema model. Key Results: The primary screen identified 16 compounds that significantly induced Wnt/β‐catenin‐dependent luciferase activity. Selected compounds activated Wnt/β‐catenin signalling without inducing cell toxicity or proliferation. Two compounds were able to promote organoid formation, which was reversed by pharmacological Wnt/β‐catenin inhibition, confirming the Wnt/β‐catenin‐dependent mechanism of action. Amlexanox was used for in vivo evaluation, and preventive treatment resulted in improved lung function and structure in emphysematous mouse lungs. Moreover, gene expression of Hgf, an important alveolar repair marker, was increased, whereas disease marker Eln was decreased, indicating that amlexanox induces pro‐regenerative signalling in emphysema. Conclusion and Implications: Using a drug screen based on Wnt/β‐catenin activity, organoid assays and a murine emphysema model, amlexanox was identified as a novel potential therapeutic agent for emphysema.